POVERTY IN NIGERIA: THE ROLE OF ECONOMIC GROWTH, GOVERNANCE AND AGRICULTURE - Osinowo, O. H.; Tolorunju, E. T.; Oyesanwen, A. A. (FUDMA JOURNAL OF SCIENCES, 2020)
Nigeria is a nation of riches with trajectories for poverty, wealth in the hands of few and extreme/abject poverty at the doorsteps of many. This study examined the role of economic growth, agriculture and quality of governance in explaining the wide differences in poverty level in Nigeria. The study used a 28-year period (1990 – 2018) time series secondary data. Data were analysed using Impulse Response Function (IRF) and Autoregressive Distributed Lag Model (ARDL). IRF revealed that there was a negative and positive response of POV to shocks in real GDP in Nigeria. ARDL showed that real GDP, inflation and unemployment are a key variables that can be used to enhanced poverty reduction and significant in both the short and long run. Similarly, education and agriculture value added also have a negative coefficient in the short run analysis which means the variables will lead to poverty reduction in the short run. The study recommended that pro poor policies should be designed for alleviating poverty and this should be cantered on diversifying the Nigerian economy with agriculture so that the benefits of economic growth will trickle down to the agro-based rural population that constitute a larger proportion of the poor people.
Keywords: Nigeria, Poverty, Economic Growth, Unemployment and ARD